Using GIS/RS techniques to Determine Suitable Sites to Construct Water Harvesting Pits in the city of Sabouraa, Hama (Damascus University Journal of agriculture sciences, 2024)
This study was conducted in district Sabouraa of the Salamiyah city, with the assistance of the laboratories of Rural Engineering and Soil Sciences Departments at Agriculture faculty, Damascus University, The reason for choosing the area is because of the scarcity of groundwater resources. The object of the study determine Suitable Sites to construct (Hafa'aer) Rainwater Harvest, The preliminary hydrological study identified an area of a watershed estimated at 624 km2, The operations of the display, digitization, analysis, interpretation, and map product were done by Arc Map 10.6.1 and make a 3D design to understand the topography of the area using Arc Scene. After collecting the data, analysis has been done (hydrological, topographic, geologic, climatic daily rainfall for 22 years). Thematic Maps have been produced (soil, Land use, curve number, slope), a field checking of these maps was also conducted, Sentinel-2 10 m satellite data was used with DEM (SRTM) 30 m digital elevation model and topographic map 1/25000 scale contains features and water streams, and the appropriate standards for the sites were set. The area of suitable sites were 119 km2, a percentage of 19% of the total area, 58 suitable sites have been selected by the suitability map and certified Standards. Then the data of rain stations were processed, and the runoff was calculated for each site to the daily precipitation and the curve number. The field check of the selected places was done, results indicate toimportance of (GIS) in rainwater harvesting studies and support decision-makers.
Keywords: Rain water Harvesting, Remote Sensing, Curve Number, Land Use.